Role of postreperfusion syndrome in the formation of postoperative complications after orthotopic liver transplantation - E. A. Kiseliova; E. F. Kim; I. A. Ushakova; G. P. Matveev; A. V. Vabishchevich (Трансплантология (Москва), 2018)
The influence of postreperfusion syndrome on the results of orthotopic liver transplantation in 100 patients who underwent to liver transplantation from living related donors and 12 recipients who underwent to retransplantation of the liver was analyzed in the retrospective study. No statistically significant differences in the dynamics of lactate levels of specific enzymes, creatinine concentration at the third postoperative day, and duration of postoperative mechanical ventilation were detected between groups with and without the postreperfusion syndrome. In this retrospective observational study there was found no effect of postreperfusion syndrome on the functional state of the transplant and on the early postoperative course.